Profit-Seeking, Individual Liability, and the Idea of the Firm - Richard A. Booth (Washington University Law Quarterly, 1995)
The thesis here is that the historical explanation for the way things are, accurate as it may be, has lost its force as an argument that things should stay that way. To be specific, (1) the line between profit-seeking and nonprofit- seeking activity is no longer as bright as it once may have been; and (2) there is nothing magical about limited liability-that is, it is no longer the definitive characteristic of the corporate form. Thus, the rather sudden emergence and astonishing growth of the LLC should be seen as part of a larger evolutionary trend in business organization law and not just as the tax tactic du jour.
Keywords: Corporations